Causes of Abortions in South American Camelids in Switzerland—Cases and Questionnaire - Isabelle Rüfli; Corinne Gurtner; Walter U. Basso; Beatriz Vidondo; Gaby Hirsbrunner; Patrik Zanolari (Animals, 2021)
Over the last decade, South American camelids (SAC) have gained increasing popularity in Switzerland. They are used for several purposes such as fiber and meat production, as companion or guard animals and for trekking activities. The purpose of this study was to investigate the frequency and reasons for pregnancy loss and perinatal death in SAC herds. Within the scope of this study, early embryonic losses could not be identified, as pregnancy examinations by ultrasonography are not performed routinely. Aborted and stillborn fetuses were collected, necropsied and analyzed for infectious abortifacients. A nationwide survey among breeders was carried out. During a 1.5-year period, only eight cases of aborted or stillborn alpaca and llama (out of a population of 6550 animals) were reported by the breeders, and their causes were subsequently analyzed. In half of the cases, Coxiella burnetii was identified in the fetoplacental material. Abortions and stillbirths were reported to be rare in Swiss herds. As a conclusion, recording of embryonic losses through ultrasound training of veterinarians should be impaired and breeders motivated to have abortions and perinatal mortality examined. Special focus should be laid on C. burnetii due to its zoonotic risk.